Incivility in Congressional Tweets. Issue 6 (November 2022) - Ballard, Andrew; DeTamble, Ryan; Dorsey, Spencer; Heseltine, Michael; Johnson, Marcus
Civility in political discourse is often thought to be necessary for deliberation and a healthy democracy. However, incivility is on the rise in political discourse in the United States—even from members of Congress—suggesting that political incivility may in fact be a tool to be used strategically. When and why, then, do members of Congress use incivility in their rhetoric? We develop and test expectations for the usage of political incivility by members of Congress on Twitter, using every tweet sent by a member of Congress from 2009–2020 coded for the presence of uncivil rhetoric via a novel application of transformer models for natural language processing. We find that more ideologically extreme members, those in safer electoral situations, and those who are in a position of political opposition are more likely to use incivility in their tweets, and that uncivil tweets increase engagement with members' messages.